Energy Analysis and Remixing Effect of Thermal Coupling Petlyuk Column for Natural Gas Liquid (NGL) Fractionation Train - Rohani Mohd Zin; Mohd Ammar Abidin; Munawar Zaman Shahruddin (International Journal of Renewable Energy Development, 2021)
In this work, a non-conventional distillation sequence with thermal coupling (Petlyuk Column) was presented as a technique to perform the separation of the NGL consist of ethane, propane, butane or other higher alkanes. The improvements were investigated through the energy analysis and remixing effect. From the result obtained, it was found that the Petlyuk arrangement consumes less amount of energy and able to reduce the remixing effects as compared to the conventional column sequencing. The Petlyuk arrangement saved about 44.49% and 12.83% in terms of cooling and heating duty, respectively. The overall annual energy saving shown by this arrangement is 39.22%. This arrangement proved to be able to prevent the remixing effect occurrence that contributes to thermal and separation inefficiency. The desired separation efficiency also obtained by this arrangement as all the product specifications are met. The ability in avoiding remixing effect by the Petlyuk column permits a significant reduction in CO2 emission with an average of 29.43 % of each equipment involved. Hence, it can be concluded that the Petlyuk arrangement model is a better alternative to be implemented in the NGL fractionation train.